Arachnoid cyst in a patient with psychosis - da Silva, Joaquim Alves (2017)
Background: The aetiology of a psychotic disturbance can be due to a functional or organic condition. Organic aetiologies are diverse and encompass organ failures, infections, nutritional deficiencies and space-occupying lesions. Arachnoid cysts are rare, benign space-occupying lesions formed by an arachnoid membrane containing cerebrospinal fluid (CSF). In most cases they are diagnosed by accident. Until recently, the coexistence of arachnoid cysts with psychiatric disturbances had not been closely covered in the literature. However, the appearance of some references that focus on a possible link between arachnoid cysts and psychotic symptoms has increased the interest in this subject and raised questions about the etiopathogeny and the therapeutic approach involved. Clinical presentation: We present the clinical report of a 21-year-old man, characterised by the insidious development of psychotic symptoms of varying intensity, delusional ideas with hypochondriac content, complex auditory/verbal hallucinations in the second and third persons, and aggressive behaviour. The neuroimaging studies revealed a voluminous arachnoid cyst at the level of the left sylvian fissure, with a marked mass effect on the left temporal and frontal lobes and the left lateral ventricle, as well as evidence of hypoplasia of the left temporal lobe. Despite the symptoms and the size of the cyst, the neurosurgical department opted against surgical intervention. The patient began antipsychotic therapy and was discharged having shown improvement (behavioural component), but without a complete remission of the psychotic symptoms. Conclusion: It is difficult to be absolutely certain whether the lesion had influence on the patient's psychiatric symptoms or not. However, given the anatomical and neuropsychological changes, one cannot exclude the possibility that the lesion played a significant role in this psychiatric presentation. This raises substantial problems when it comes to choosing a therapeutic strategy.